2007
DOI: 10.1007/s11746-007-1178-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Analytical Methods for Assessing Antioxidant Capacity of Rapeseed and Olive Oils

Abstract: The oxygen radical absorbance capacity (ORAC) and the ferric reducing antioxidant power (FRAP) methods were used for the determination of antioxidant capacities (AC) of rapeseed oils at different steps of technological process and olive oils. The mean ORAC and FRAP results obtained for rapeseed oils (1,106-160 and 552-95.6 lmol TE/100 g) were higher than for olive oils (949-123 and 167-32.1 lmol TE/100 g). Although, FRAP values were lower than ORAC values for all studied oils, there is a linear and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 17 publications
(37 reference statements)
8
91
1
8
Order By: Relevance
“…Os antioxidantes naturais de óleos vegetais apresentam potencial efeito na prevenção de doenças crônicas, pois são capazes de proteger sistemas biológicos contra a ação de espécies reativas de oxigênio e nitrogênio, responsáveis por danos oxidativos aos lipídeos, proteínas e ácidos nucleicos 1,2 . Além de apresentarem bioatividade no organismo humano, os antioxidantes naturais protegem os óleos vegetais contra a ação de radicais livres que iniciam e perpetuam a peroxidação lipídica, que consiste na principal forma de degradação dos óleos vegetais e em importante fonte de prejuízos para a indústria de alimentos 3 .…”
Section: N T R O D U ç ã Ounclassified
See 3 more Smart Citations
“…Os antioxidantes naturais de óleos vegetais apresentam potencial efeito na prevenção de doenças crônicas, pois são capazes de proteger sistemas biológicos contra a ação de espécies reativas de oxigênio e nitrogênio, responsáveis por danos oxidativos aos lipídeos, proteínas e ácidos nucleicos 1,2 . Além de apresentarem bioatividade no organismo humano, os antioxidantes naturais protegem os óleos vegetais contra a ação de radicais livres que iniciam e perpetuam a peroxidação lipídica, que consiste na principal forma de degradação dos óleos vegetais e em importante fonte de prejuízos para a indústria de alimentos 3 .…”
Section: N T R O D U ç ã Ounclassified
“…O ensaio do FRAP tem sido utilizado principalmente para determinação da capacidade antioxidante na fração polar de óleos vegetais ricos em compostos fenólicos, como azeite de oliva e óleo de canola 1,24 , pois o reagente do ensaio do FRAP é incompatível com os solventes orgânicos utilizados para dissolver óleos ou sua fração apolar 6 . Recentemente, Jimenez-Alverez et al 19 reportaram o uso de β-ciclodextrina aleatoriamente metilada para dissolver adequadamente a fração apolar de orégano e permitir a reação desse extrato com o reagente do FRAP.…”
Section: Espin Et Alunclassified
See 2 more Smart Citations
“…Moreover, the activity of individual phenolic compounds also varies. Studies indicate a significant correlation of contents of these compounds and antioxidant stability of these oils (Mińkowski et al, 2013;Szydłowska-Czerniak et al, 2008). Siger et al (2008) also showed correlations between phenolic contents in oils and their antioxidant activity and free radical scavenging capacity.…”
Section: Antioxidant Activitymentioning
confidence: 89%